Inflammatory Acute Response. Biochemical and Cellular Considerations - Milagros Lisset León Regal; Ania Alvarado Borges; José Omar de Armas García; Luciano Miranda Alvarado; Javier Antonio Varens Cedeño; José Ángel Cuesta del Sol (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
The acute inflammation constitutes a natural, protective-character response that intends to free the organism of the initial cause of the cell lesion and of the consequences that it provokes. The present work aimed at argumenting on the mechanisms that explain the vascular changes, and the establishment of the signs of the acute inflammatory response with an in-depth molecular level. 18 articles of scientific magazines, 2 books and other sources of information that was accessed by means of the principal managers of the computer network, adding up a total of 20 sources, were consulted. Right after a cell lesion; a complex group of biochemical and cell interactions begins, mediated for the activity of multiple chemical agents, which provoke changes in the microvasculature, as well as an increasement of leucocytes at the lesion's zone, and finally the acute inflammatory response's signs.